2021
DOI: 10.1038/s41422-021-00506-9
|View full text |Cite
|
Sign up to set email alerts
|

The metabolite α-KG induces GSDMC-dependent pyroptosis through death receptor 6-activated caspase-8

Abstract: Pyroptosis is a form of regulated cell death mediated by gasdermin family members, among which the function of GSDMC has not been clearly described. Herein, we demonstrate that the metabolite α-ketoglutarate (α-KG) induces pyroptosis through caspase-8-mediated cleavage of GSDMC. Treatment with DM-αKG, a cell-permeable derivative of α-KG, elevates ROS levels, which leads to oxidation of the plasma membrane-localized death receptor DR6. Oxidation of DR6 triggers its endocytosis, and then recruits both pro-caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
155
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(156 citation statements)
references
References 64 publications
1
155
0
Order By: Relevance
“… 31 Interestingly, caspase‐8 can also shear gasdermin C (GSDMC) into GDSMC NT fragments and subsequently switch apoptosis to pyroptosis in breast cancer cells with TNF‐α treatment. 32 Consistently, Zhang et al 33 recently showed that the caspase‐8, which is recruited to ROS‐oxidized and internalized death receptor 6 (DR6) after application with dimethyl‐α‐ketoglutarate (DM‐α‐KG), can cleave GSDMC at Asp240 and subsequently trigger GSDMC‐mediated pyroptotic cell death in many human gastric cancer cells (SGC‐7901 and BGC‐823), human colon cancer cells (HCT116) and human hepatoma cells (Huh7).…”
Section: Pyroptosismentioning
confidence: 62%
See 1 more Smart Citation
“… 31 Interestingly, caspase‐8 can also shear gasdermin C (GSDMC) into GDSMC NT fragments and subsequently switch apoptosis to pyroptosis in breast cancer cells with TNF‐α treatment. 32 Consistently, Zhang et al 33 recently showed that the caspase‐8, which is recruited to ROS‐oxidized and internalized death receptor 6 (DR6) after application with dimethyl‐α‐ketoglutarate (DM‐α‐KG), can cleave GSDMC at Asp240 and subsequently trigger GSDMC‐mediated pyroptotic cell death in many human gastric cancer cells (SGC‐7901 and BGC‐823), human colon cancer cells (HCT116) and human hepatoma cells (Huh7).…”
Section: Pyroptosismentioning
confidence: 62%
“…Chemotherapeutics, such as doxorubicin, lobaplatin, cisplatin and tetraarsenic hexoxide, can suppress the growth of neuroblastoma, melanoma, colon cancer cells and breast cancer by inducing GSDME‐mediated pyroptosis. 85 , 86 , 87 , 88 Recently, Zhang et al 33 showed that intratumoral injection of DM‐αKG can notably repress tumour growth and metastasis through caspase‐8‐GSDMC‐mediated pyroptosis. Moreover, GSDME/GSDMB‐dependent pyroptosis is implicated in cytotoxic T lymphocytes or chimeric antigen receptor (CAR) T cell‐mediated antitumour immunity.…”
Section: Pyroptosis In Noninfectious Diseasesmentioning
confidence: 99%
“…GSDMC is primarily cleaved by Caspase-8 (Hou, Zhao et al 2020, Zhang, Zhou et al 2021). Indeed, the pattern of bands of cleaved GSDMC-2/-3 is compatible with the activity of Caspase-8 (Julien and Wells 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Hepatic NOD2, a well-characterized intracellular PRR of the NOD-like receptor (NLR) family, has been shown to promote hepatocarcinogenesis [ 41 ]. In addition, GSDMC, metabolized by α -ketoglutarate and mediated through caspase-8, results in pyroptosis [ 42 ]. Overall, increasing studies have confirmed the roles of these genes (DHX9, CHMP4B, BAK1, NOD2, and GSDMC) in HCC.…”
Section: Discussionmentioning
confidence: 99%